Peran Hidden Curriculum dalam Membentuk Kesadaran Ekoteologi Mahasiswa Pendidikan Agama Islam - Rifki Auliak; Citra Dewi Maharani Azzahro; Muhammad Ihsan Siregar; Sabarudin (Institut Kariman Wirayudha Sumenep, 2026)
Ecotheological awareness in Islamic education is formed not only through the formal curriculum but also through the hidden curriculum present in the culture and practices of campus life. This study used a qualitative approach with a transcendental phenomenological design. Data were obtained through in-depth interviews, participant observation, and documentation studies, then analyzed using Clark Moustakas' transcendental phenomenological model. The findings indicate that ecotheological awareness of Islamic Education (PAI) students at INSIMA Majenang is formed through campus religious culture, lecturers' role models, hygiene habits, and daily social experiences. Contradictory experiences that do not reflect ecological values ​​actually encourage critical reflection, leading to a more reflective and transformative understanding of ecotheological awareness. This awareness is actualized in ecological behaviors such as maintaining environmental cleanliness, reducing the use of single-use plastics, maintaining campus facilities, and increasing environmental awareness. The hidden curriculum plays a significant role in the formation of students' ecotheological awareness. This study resulted in the concept of the Reflective Ecotheological Internalization Model and Spatial Exam Pedagogy, which explains that both positive and contradictory experiences can be a means of forming ecological awareness based on Islamic values.